Dependence of the Efficiency of Triplet-Triplet Energy Transfer on the Distance Between the Donor and Acceptor - Ibraev, N.Kh.; Seliverstova, E.V.; Artyukhov, V.Ya. (SPRINGER, 2015)
The triplet-triplet and singlet-singlet energy transfer is investigated both experimentally and theoretically in the anthracene - Nile red system. Quantum-chemical investigations of the special features in the formation of electronically excited states and photoprocesses in the donor-acceptor pair are performed. It is demonstrated that atypical distance dependence of the efficiency of triplet-triplet energy transfer in the Langmuir-Blodgett multilayered thin films is caused by additional quenching of donor particles due to the process of energy transfer to acceptor centers by the inductive-resonant mechanism.
Keywords: energy transfer; Langmuir–Blodgett film; quantum-chemical calculations